THE INFLUENCE OF POSITIVE THINKING ON STRESS POST THE DEATH OF PARENTS IN ADOLESCENTS AT AL-ITTIHADIYAH PRIVATE HIGH SCHOOL MEDAN - Siska Dwi Ningsih; Henny Arwina Bangun; Winny Sunfriska br Limbong; Mita Damayanti (RADJA PUBLIKA, 2024)
Parents are the figures closest to children. The task of raising children is not an easy thing, it requires cooperation between mother and father. A warm home atmosphere and feeling safe are basic needs in family life. With these basic needs, these must be fulfilled so that you always feel calm, safe and comfortable. This study aims to determine the effect of positive thinking on stress after the death of a parent in adolescents at Al-Ittihadiyah Medan Private High School. The research method used in this research is quantitative research. The location of the research was Medan Private High School, which is located at Jl. Arca Building No. 55 Medan, Teladan Barat, District. Medan City, Medan City, North Sumatra Province. The population in this study was 30 people and all of them were used as samples. The results of the research show that there is an influence of positive thinking on stress after the death of a parent in teenagers at Al-Ittihadiyah Medan Private High School with a p-value of 0.000<0.05.